2013
DOI: 10.1631/jzus.a1300010
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and multi-objective optimization of a gasoline engine using neural networks and evolutionary algorithms

Abstract: Abstract:In this paper, a multi-objective particle swarm optimization (MOPSO) algorithm and a nondominated sorting genetic algorithm II (NSGA-II) are used to optimize the operating parameters of a 1.6 L, spark ignition (SI) gasoline engine. The aim of this optimization is to reduce engine emissions in terms of carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NO x ), which are the causes of diverse environmental problems such as air pollution and global warming. Stationary engine tests were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…The NSGA-II genetic algorithm was used for the multi-objective optimization involving the maximization of NO x conversion efficiency while minimizing NH 3 slip because it has proven to give better optimal results compared with other optimization methods as observed in references [23,24].…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSGA-II genetic algorithm was used for the multi-objective optimization involving the maximization of NO x conversion efficiency while minimizing NH 3 slip because it has proven to give better optimal results compared with other optimization methods as observed in references [23,24].…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…The support vector machine (SVM), which is established based on the structural risk minimization principle, has proven to exhibit better generalization performance than neural networks and other methods [22]. In the work of Martinez-Moraleset [23], artificial neural networks were used for the non-linear identification of a gasoline engine for the purpose of evaluating objective functions used within an optimization framework involving the use of the NSGA-II genetic algorithm and the Multi-Objective Particle Swarm Optimization (MOPSO) algorithm. It was observed that the NSGA-II algorithm performed better than the MOPSO algorithm in the Pareto based optimization process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evolution multiobjective optimization, which applies evolution computation to multiobjective optimization has attracted a great deal of attention (Feng et al, 2010;Cheng et al, 2013;Martínez-Morales et al, 2013;Gao et al, 2014). Many multiobjective genetic algorithms have been proposed.…”
Section: External Interactions Independence Viewpointmentioning
confidence: 99%
“…In addition to filter algorithms, there exists an abundance of algorithms for RUL estimation based on statistical theory and pattern recognition, such as Bayesian theory [25][26][27], neural networks (NN) and various transformers [16,28], support vector machine (SVM) algorithms [19,25,29,30], etc. The NN and SVM algorithms both have remarkable advantages in dealing with nonlinear modeling problems.…”
Section: Introductionmentioning
confidence: 99%